Analysis of the Competence of Tour Leader Svarga Tour and Travel on the Smooth Departure Process of Umrah Pilgrims at Adi Soemarmo Airport - Muhammad Fadhil Rodhianto; Aditya Dewantari (CV. Civiliza Publishing, 2026)
The success of the Umrah pilgrims' departure process is influenced not only by the operational system of travel companies but also by the competence of Tour Leaders as the primary companions of pilgrims. Tour Leaders play an essential role in ensuring that each departure stage, from document verification to boarding procedures, is conducted effectively according to established standards. This study aims to analyze the competence of Tour Leaders in supporting the smooth departure process of Umrah pilgrims at Adi Soemarmo Airport, managed by Svarga Tour and Travel, as well as to identify the challenges faced by Tour Leaders and the obstacles experienced by pilgrims during the departure process. This study employed a descriptive qualitative approach. Data were collected through semi-structured interviews, observations, and documentation involving five purposively selected informants consisting of Tour Leaders, an Operational Manager, and Umrah pilgrims. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that Tour Leader competence, including knowledge, communication skills, coordination abilities, problem-solving skills, and professional attitudes, significantly contributes to the smooth departure process of Umrah pilgrims. The main challenges include incomplete travel documents, schedule changes, late arrival of pilgrims, and differences in pilgrim characteristics. This study highlights the importance of Tour Leader competence as an operational factor in improving the effectiveness of Umrah departure services at airports.